2012
DOI: 10.3390/ijms13089489
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Differential Levels of Proteins in the Urine of Patients with Endometrial Cancer: Analysis Using Two-Dimensional Gel Electrophoresis and O-Glycan Binding Lectin

Abstract: Cancers can cause some proteins to be aberrantly excreted or released in the urine, which can be used as biomarkers. To screen for potential biomarkers for endometrial cancer (ECa), the urinary proteins from patients who were newly diagnosed with early stage ECa and untreated controls were separated using two-dimensional gel electrophoresis (2-DE) and followed by image analysis. The altered levels of zinc alpha-2 glycoprotein, alpha 1-acid glycoprotein, and CD59 were detected in the patients compared to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Data for the identification of the kininogen (KNG) spot cluster had been previously reported [7]. Analysis of the volumes of the proteins showed that the levels of LRG and CLU in the OCa patients were both 17-fold higher than the controls, while the level of the patients’ KNG was six-fold lower than the controls (Table 2).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Data for the identification of the kininogen (KNG) spot cluster had been previously reported [7]. Analysis of the volumes of the proteins showed that the levels of LRG and CLU in the OCa patients were both 17-fold higher than the controls, while the level of the patients’ KNG was six-fold lower than the controls (Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…CGB lectin was purified as previously described [7,8]. Briefly, crude extracts of the seeds of champedak were prepared by stirring of homogenized seeds in PBS, pH 7.4, overnight, and subjecting the supernatant to 60% ammonium sulfate precipitation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bladder [21],Ovarian [22] Urine, Blood P02764 P02763 Alpha-1-acid glycoprotein (A1AG) Yes endometrial [23], bladder [24], lung [25] Urine, blood not peer-reviewed) is the author/funder. All rights reserved.…”
Section: Mrm Verificationmentioning
confidence: 99%